Gugon Tuhon sebagai Kearifan Lokal Masyarakat Kecamatan Paninggaran Kabupaten Pekalongan - Nia Himatul Ulfa; Naura Fatkhiana Rif’an; Annissa Meilasari; Tiara Nur Khikma; Dimas Setiaji Prabowo (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
Gugon tuhon is one form of local wisdom among the Javanese people that acts as an unwritten set of norms in regulating social interaction patterns. This study aims to describe the forms, meanings, and functions of gugon tuhon among the people of Paninggaran Subdistrict, Pekalongan Regency, with a focus on three taboos: sitting on the doorstep, eating on the bed, and lying down around Maghrib time. The method used is a descriptive qualitative approach with an ethnopragmatic design, combining literature studies, field observations, and in-depth interviews with traditional elders, community leaders, and the younger generation. The results show that these three taboos contain rational values covering safety, health maintenance, and religious ethics, which are presented through mystical expressions to make them easier to understand and pass down through generations. The novelty of this research lies in the effort to document local sayings in the Paninggaran area, which have rarely been touched by academic research, while also connecting them to Indonesian language and literature learning based on local wisdom. This study is expected to contribute to the preservation of oral traditions, the development of local content teaching materials, and the strengthening of character education in schools.